Managing fish species under threat: case studies from the Native Fish Strategy for the Murray‐Darling Basin, Australia. (March 2014) - Lintermans, Mark; Lyon, Jarod P.; Hames, Fern; Hammer, Michael P.; Kearns, Joanne; Raadik, Tarmo A.; Hall, Arkellah
Summary: The Native Fish Strategy (NFS) for Australia's Murray‐Darling Basin was specifically targeted at managing and rehabilitating an entire fish community. Over half of the native fishes (24 of 44 known species) and four fish communities of the Murray‐Darling Basin (MDB) are listed as threatened at either national or state level. One of six 'Driving Actions' under the NFS focused on protecting threatened native fish species, and this study reviews a series of NFS case studies during and immediately after the Millennium Drought (1997–2010) which was south‐eastern Australia's worst drought on record. Fish rescues, breeding programmes, the creation of an emergency response contingency fund, and expert panels and workshops were all projects that contributed significantly to conserving threatened fishes. The diversity of approaches taken and lessons learned are highlighted, to formulate future directions for threatened fish recovery.